The Impact of the Work Environment on the Productive Efficiency of Faculty Members: An Applied Study on the Faculties of Business Administration and Law at the University of Jufra - Mataly, Manar (Journal of Pure & Applied Sciences, 2025)
The study aimed to evaluate the impact of the work environment on the productive efficiency of faculty members in the Faculties of Business Administration and Law at the University of Jufra, using a questionnaire distributed to 40 faculty members. The results showed negative impressions about administrative support, with a lack of material and logistical support. The social environment was generally positive, but with dissatisfaction with the administration's response to suggestions. The results indicated a lack of resources, technology, and office space. However, faculty members expressed satisfaction with their productive efficiency. There was no direct effect of administrative support on productive efficiency, with a slight, non-statistically significant association between the social environment and productive efficiency, and a moderate, non-statistically confirmed association between the physical environment and productive efficiency. Recommendations included improving administrative support, developing mechanisms for responding to suggestions, improving the physical environment, strengthening social relations, and conducting additional studies to determine the factors that most affect productive efficiency.